The Question of Stress Marking Among San Marcos First-year Students - Portilla, Luisa (2004)
This article considers variables at work when first-level universitystudents make mistakes when writing a tilde over words. The authoroffers sorne recommendations and a pedagogical propasa! to cope with theproblem.